From the Fronts of Expansion to Large Development Projects: An Emergency in the Communities of the sertões of Itacuruba - Poliana de Sousa Nascimento (Íconos)
This article is the result of reflections about the large development projects installed in sertão of Itaparica, Pernambuco state, Brazil. It analyses the ways in which a development discourse through the years has stimulated forceful displacements and the appropriation of natural resources, affecting the physical, social, and cultural modes of reproduction of peoples and traditional communities. It provides an analytical perspective based on ponderations that emerge from fronts promoted by the State to expand the implementation of new spaces for these large economic development projects that are legally backed. The forms of territorial appropriation are linked to the discourse of “open spaces” and the decadent spaces that are associated with the sertões of Brazil since the 16th century, in order to make the implementation of economic enterprises in the regions, considered at the margin of capital, effective.